The down-to-earth guide to global warming - David, Laurie; Gordon, Cambria (New York : Orchard Books, 2007)
Describes why global warming happens, how it affects the planet, and measure that can be taken to stop it.
Includes bibliographical references (p. 106-107) and index.
Keywords: Global warming -- Juvenile literature; Global warming